Influence Of Shop Spatial, Product Variation, Product Design And Service Quality Repurchase Interest In Zero Outlet Garut - McGuire, Stephen J. J; Zhang, Yang; Putra, Zulkornain Yusop (Yayasan Pendidikan Belajar Berdikari, 2022)
The purpose of this study is to ascertain the impact of store design, product diversity, product design, and service quality on consumers' desire to make additional purchases at Zero Outlet Garut. Structural Equation Modeling (SEM), also known as visual rendition 3.0 Partial Least Square (PLS), was utilized in this investigation as a method of information verification. The conclusion of this study demonstrates a positive and significant relationship between store layout and repurchase intention, with a t-count > 1.96 and a result of 0.215. Where the result is 0.285 with a t-statistic value > 1.96, which is 2.769, and a big level of 0.002, the effect of product variation on repurchase intention is positive and substantial. Effect of product design on repurchase intention with a positive value and sig., where the coefficient is 0.235 and the t- statistic is greater than 1.96, with a critical level of 0.049 to 0.050. The coefficient is 0.203, the t statistic is 2.147, the standard t table value is 1.96 with the sign being 0.032 0.050, and the influence of service quality on repurchase intention is positive and significant.